Small round blue cell tumor of the lung: the challenge - Dos Santos, J; Teixeira, C; Amaro, T (Citotech Online - Case Review, 2023)
Small cell carcinoma of the lung is a high grade neuroendocrine tumor that corresponds to 10-15% of lung cancer cases. It is an aggressive tumor that grows rapidly, arises predominantly in the hilum of smokers and is characterized by poor prognosis. Although the cytological features of small cell carcinoma of the lung are well described, it may be a challenge to distinguish it from other neoplasms by cytological examination and this distinction carries significant clinical importance. We present a case of a 70-year-old man with endobronchial lesion and paratracheal adenopathies. Based on liquid-based cytology (bronchial washing and brushing), a small cell carcinoma of the lung was diagnosed, using complementary immunocytochemistry techniques. The patient was treated with chemotherapy, radiotherapy and corticotherapy and is currently with metastatic disease and poor general state.